TINJAUAN PELAKSANAAN IMPOR COIL MELALUI FREIGHT FORWARDER PADA PT CHITA INDONESIA DI BEKASI - Niantoro Sutrisno; Didit Saputro (POLITEKNIK LP3I JAKARTA, 2018)
ABSTRACT This study entitled Implementation of Imports Imports Coil Through Freight Forwarder At PT Chita Indonesia In Bekasi. This research uses qualitative descriptive method in which the authors do research by way of data collection, analyze data, and describe the data systematically for easy to understand. The author presents a description of the problem based on facts, data, phenomena, and circumstances that occur when the study goes with what it is. The purpose of this study is to know the Implementation, Obstacles and provide recommendations on Import activities conducted through a third party, namely Freight Forwarder.From the results of this study it can be concluded that Implementation of Coil Imports using Freight Forwarder Services at PT Chita Indonesia has been running well, but it needs improvement in some activities so that problems that become constraints can be overcome. While the obstacles that occur more dominant on errors in the document. For that reason, the recommendation given is the making of SOP so that errors in the case of documents made by internal parties can be minimized, a firm stance against the freight forwarder in case of mistakes made by the freight forwarder or add another freight forwarder as the benchmark service of the freight forwarder used. Keywords: Import, Coil, Freight Forwarder